SAFe coaches handbook : practical tips and techniques for launching and running SAFe teams, arts, and agile enterprises /: practical tips and techniques for launching and running SAFe teams, arts, and agile enterprises. (2023) - Wilmshurst, Darren; Quick, Lindy; McMillan, Keith
No abstract available